The causality between inflation and unemployment: The Indonesian evidence - Gatot Sasongko; Andrian Dolfriandra Huruta (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Two closely watched indicators of economic performance are inflation and unemployment. This study empirically analyzes the causality between inflation and unemployment in Indonesia during 1984 to 2017. The data were gathered from the Indonesian Central Bureau of Statistics. Methodologically, this study employed the Granger Causality test and Vector Autoregression to determine the causality between inflation and unemployment. The results show that there is a one-way causality between inflation and unemployment. The findings imply that unemployment causes inflation, but not vice versa. Next inflation and unemployment are also closely related to other determining factors, such as season, household income, and the decisions to attend school or to perform the housekeeping.
Keywords: E600; E610; 650; granger causality; inflation; unemployment; vector autoregression